Emerging water pollution in the world's least disturbed lakes on Qinghai-Tibetan Plateau. (1st March 2021) - Wu, Yue; Wang, Shengrui; Ni, Zhaokui; Li, Hong; May, Linda; Pu, Jia
Abstract: Qinghai-Tibet Plateau (QTP) Lake Region has largest abundance and size distribution of lakes in China. Being relatively away from major human activities, the water quality of these lakes has not attracted concerns in the past. However, dramatic climate change and intensified anthropogenic activities over the past 30 years have exerted multiple pressures on the water environment of the lakes, resulting in elevated nutrient concentrations in major freshwater lakes of the region. Rapid water quality deterioration and eutrophication of the lakes were first found in Lake Hurleg in the northeast of the plateau. Analyses of driving forces associated with these changes indicate that both the intrinsic characteristics of the QTP lakes and climate change were responsible for the vulnerability to human activities than other lakes in different regions of China, with accelerated urbanization and extensive economic development in the lake basin playing a decisive role in creating water pollution events. Under combination pressures from both natural and anthropogenic effect, the increasing rate of nutrient concentrations in Lake Hurleg has been 53–346 times faster than in Lake Taihu and Lake Dianchi during the deterioration stage. The result suggests the current development mode of Lake Hurleg basin is not suitable for setting protection targets for the QTP lake region more broadly due to its extremely poor environmental carrying capacity. To stop worsening the lake water environment condition, it is necessary to review the achievements made and lessons learned from China's fight against lake pollution and take immediate measures, inform policies into the development mode in the QTP lake region, and avoid irreversible consequences and ensure good water quality in the "Asian Water Tower." Graphical abstract: Image 1 Highlights: Raised concentration of N and P in Qinghai-Tibetan lakes since 1990 was identified. Initially recorded water pollution was induced by intensified human activities. Lake morphology and climate internally determined the fragility of QTP lakes. Management and development modes should be transformed in this region. Abstract : Decline of water quality occurred in QTP lakes, current regional development mode is unsuitable for the protection of these lakes.